2006
DOI: 10.1136/jcp.2005.034181
|View full text |Cite
|
Sign up to set email alerts
|

High stromal versican expression predicts unfavourable outcome in oral squamous cell carcinoma

Abstract: Background: Versican, an extracellular matrix proteoglycan, has been noted to be expressed in several malignant tumours and has been suggested to play an important role in cancer development and tumour growth. Aims: To investigate whether the versican expression level in the peritumoural stromal tissue of primary oral squamous cell carcinoma (OSCC) predicts relapse-free or disease-specific survival. Also, to study the associations between versican expression and several other clinicopathological variables, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 36 publications
1
37
0
3
Order By: Relevance
“…44 This suggests that versican might act as a molecular sink, trapping CCL5 and CCL21, and offers We also have associated the expression of versican with relevant clinical parameters such as lymph node metastasis, tumor size, infiltration depth and vascular space involvement. Although for breast, cervical, prostate and other tumor types, increased versican expression has been associated with relapse and poor clinical outcome, 12,16,17,19,20,36,39,45,46 we could not demonstrate this association in our cervical cancer cohort. To exclude that this was related to the scoring system, we have also scored our data according to the method described by Kodama et al 20 (data not shown), but in this case also no statistically significant association was found.…”
Section: Versican In Cervical Carcinomamentioning
confidence: 63%
See 1 more Smart Citation
“…44 This suggests that versican might act as a molecular sink, trapping CCL5 and CCL21, and offers We also have associated the expression of versican with relevant clinical parameters such as lymph node metastasis, tumor size, infiltration depth and vascular space involvement. Although for breast, cervical, prostate and other tumor types, increased versican expression has been associated with relapse and poor clinical outcome, 12,16,17,19,20,36,39,45,46 we could not demonstrate this association in our cervical cancer cohort. To exclude that this was related to the scoring system, we have also scored our data according to the method described by Kodama et al 20 (data not shown), but in this case also no statistically significant association was found.…”
Section: Versican In Cervical Carcinomamentioning
confidence: 63%
“…Versican expression was normalized against a household gene (EEF1A1). 12,13,[16][17][18]20,23,34,[36][37][38][39] As the composition of the ECM influences the migration of inflammatory cells, 33 we have also measured the association between inflammatory cells and versican expression. Despite the reported production of versican isoforms V0 and V1 by human leukemic monocytes 40 and the reported …”
Section: Discussionmentioning
confidence: 99%
“…These have been found to regulate cancer cell behavior and affect disease outcome in a number of malignancies, including cancers of the lung, breast, ovary, mouth, pharynx and skin. [10][11][12][13][14][15] Previous studies have shown that expression of versican, a chondroitin sulfate proteoglycan, is increased in prostate cancer and inhibits cancer cell adhesion to fibronectin in the stromal matrix. 16,17 Furthermore, high performance liquid chromatography analysis of glycosaminoglycans extracted from prostate cancer samples revealed that chondroitin-6-sulfate and dermatan sulfate were the predominantly upregulated components.…”
mentioning
confidence: 99%
“…Thus, depending on the context, ADAMTS proteases may primarily mediate versican clearance or contribute to both versican clearance and the generation of bioactive versican fragments. Further, Pukkila M. et al [15] investigated whether the versican expression level in the peritumoural stromal tissue of primary oral squamous cell carcinoma (OSCC) predicts relapse free or disease specific survival.They also studied the associations between versicanexpression and several other clinicopathological variables as well as tumour cell proliferation. The results from this study supported the hypothesis that strong stromal versican expression is an adverse prognostic sign in OSCC.…”
Section: Mmps and Adamtsmentioning
confidence: 99%